Human iPSC-derived Down syndrome astrocytes display genome-wide perturbations in gene expression, an altered adhesion profile, and increased cellular dynamics. (15th January 2020) - Ponroy Bally, Blandine; Farmer, W Todd; Jones, Emma V; Jessa, Selin; Kacerovsky, J Benjamin; Mayran, Alexandre; Peng, Huashan; Lefebvre, Julie L; Drouin, Jacques; Hayer, Arnold; Ernst, Carl; Murai, Keith K
Abstract: Down syndrome (DS), caused by the triplication of human chromosome 21, leads to significant alterations in brain development and is a major genetic cause of intellectual disability. While much is known about changes to neurons in DS, the effects of trisomy 21 on non-neuronal cells such as astrocytes are poorly understood. Astrocytes are critical for brain development and function, and their alteration may contribute to DS pathophysiology. To better understand the impact of trisomy 21 on astrocytes, we performed RNA-sequencing on astrocytes from newly produced DS human induced pluripotent stem cells (hiPSCs). While chromosome 21 genes were upregulated in DS astrocytes, we found consistent up- and down-regulation of genes across the genome with a strong dysregulation of neurodevelopmental, cell adhesion and extracellular matrix molecules. ATAC (assay for transposase-accessible chromatin)-seq also revealed a global alteration in chromatin state in DS astrocytes, showing modified chromatin accessibility at promoters of cell adhesion and extracellular matrix genes. Along with these transcriptomic and epigenomic changes, DS astrocytes displayed perturbations in cell size and cell spreading as well as modifications to cell-cell and cell-substrate recognition/adhesion, and increases in cellular motility and dynamics. Thus, triplication of chromosome 21 is associated with genome-wide transcriptional, epigenomic and functional alterations in astrocytes that may contribute to altered brain development and function in DS.